Community perception of the benefits and quality of services rendered by College of Nursing students of Siliman University - Turtal, Rowena M.; Cagara, Rochie C.; Gloria, Grace A.; Pyponco, Chereisle G.; Cardimas, Jocelyn C.; Logronio, Jane J. (2013)
This study primarily aims to assess the benefits and quality of services rendered by Silliman University College of Nursing (SUCN) students in three barangays (villages) of Valencia, Negros Oriental, Philippines. The quantitative data were obtained through an interview schedule, from 236 respondents who were randomly selected from the three barangays. Purposive sampling was utilized to determine the participants of the focus group discussion (FGD) which consisted of formal leaders and leaders of organized groups. Quantitative data were analyzed using descriptive statistics (mean) while content analysis was used to analyze the data from the FGDs. The result of the assessment on the quality of services was interpreted as very good (mean = 3.35) while the assessment on the level of benefits of services was interpreted as very beneficial (mean = 3.42). The qualitative findings revealed that the presence of SUCN students in the three barangays influenced certain changes in health practices, and that knowledge and skills on health promotion and illness prevention were gained from the students.